Chronic kidney disease in patients with recurrent nephrolithiasis and concomitant damage to the cardiovascular system - R. V. Royuk; S. K. Yarovoy (Вестник урологии, 2021)
Introduction. Chronic kidney disease (CKD) is commonly diagnosed in patients with cardiovascular diseases (CVDs) and also manifests itself in most patients with urolithiasis. Numerous studies have shown that renal dysfunction is not only directly related to the high risk of developing various CVDs and chronic heart failure (CHF) as one of the most common complications but also the mortality rate in comorbid patients. CKD and CHF have similar pathogenetic mechanisms and common target organs; co-existing, both pathological conditions accelerate the progression of major diseases and significantly aggravate their course. In patients with recurrent nephrolithiasis combined with CVDs, all the causes leading to the formation of CKD (recurrent obstructive pyelonephritis, nephroangiosclerosis, etc.) are present to some extent.Purpose of the study. To evaluate the incidence and characteristics of CKD in patients suffering from recurrent urolithiasis associated with CVDs.Materials and methods. The prospective study included 406 patients who were treated for recurrent nephrolithiasis and concomitant CVDs from 2007 to 2020 (Urology Division, Burdenko Principal Military Clinical Hospital). From long-term follow-up respondents who lived at least 10 years after inclusion in the study (n = 52), three groups were formed: group I (n = 18) included patients with a combination of essential hypertension (EH) and ischemic heart disease (IHD), complicated by CHF; group II (n = 15) consisted of patients with uncomplicated CVDs (EH – 7 patients, IHD – 8 patients). The control group III (n = 19) included respondents suffering from nephrolithiasis without CVDs. The glomerular filtration rate (GFR) was determined by the CKD-EPI (Chronic Kidney Disease Epidemiology Collaboration) following the Russian National Guidelines for «Chronic Kidney Disease». The analysis of the obtained data was carried out using Statistica 8.0; the Fisher and Wilcoxon criteria were calculated; the differences were considered significant at p < 0.05.Results. All patients included in the study were repeatedly hospitalized urgently and as planned and underwent at least one non-invasive manipulation or surgery. The average age of the patients was 58.9 ± 2.95 years; men predominated (~ 75 – 78%). A GFR decrease was recorded in 41.1% of patients included in the study, in 40.5% of patients with a combination of nephrolithiasis and uncomplicated CVDs, Also, its decrease was found in 60 (58.8%) of patients with chronic heart failure (CHF) in 41.1% of cases from the general sample and 40.5% of patients without CHF. CKD stage II occurred in 44 (43.1%) cases of CHF; CKD stages III Ca and Cb were detected in 10 (9.8%) and 4 (1%) cases, respectively; CKD stage IV developed in 1 (0.25%) patient with one of the re-hospitalizations. Of the 52 patients included in the second study part, the ratio of men and women was 41/11 (78.8 and 21.2%, respectively). All three groups were also dominated by men. The initial values of GFR in group I patients significantly differed from those in the control group; in group II, statistically significant differences appeared 4 years after the s the study initiation, and in group I – after 2 years. A sharp (1.5-fold) significant decrease in renal filtration function was registered in group I by the 6th research year, in group II (1.3-fold) – by the 8th research year, and in group III (1.28-fold) – only by the 10th research year. The GFR level in group I and group II decreased during the 1st follow-up year by 2.36 and 1.65 times, respectively.Conclusion. CKD in patients suffering from recurrent nephrolithiasis in combination with IHD and EH is generally benign. The progression rate of filtration deficiency is relatively low and is (at least in the early stages) about 4.5 ml/min per year. The addition of CHF increases the rate of decline in renal filtration function by up to 25% (from 4 ml/min per year to 5 ml/min per year). The main negative effect of concomitant CVDs (especially complicated CHF) is not an ultrahigh decrease in GFR but a reduction in kidney functioning stable period up to complete cessation.